Characteristics of stroke service implementation in Armenia - Sahakyan, Greta; Orduyan, Mira; Badalyan, Sevak; Adamyan, Ani; Hovhannisyan, Mariam; Manucharyan, Hasmik; Egoyan, Sagatel; Makaryan, Yuri; Manvelyan, Hovhannes (Frontiers in Neurology, 2023)
Background: Acute stroke care service in Armenia was established in 2019 after the implementation of the National Stroke Program (NSP). This study aimed to provide an up-to-date account of the current image and clinical characteristics of acute stroke service implementation at a tertiary hospital in Armenia by analyzing the quality of care and identifying the areas that need improvement. Methods: We analyzed patient data of a single hospital in one year after the establishment of acute stroke care service (February 2021-January 2022). We selected patients who were within 0-24h from symptom onset at admission and included patients who benefited from reperfusion therapies (intravenous thrombolysis (IVT) and/or endovascular thrombectomy (EVT)). A favorable outcome was defined as a drop of the National Institutes of Health Stroke Scale (NIHSS) by more than 4 points at discharge and a modified Rankin Score (mRS) of 0-2 at 90 days. Results: Of the total 385 patients, 155 underwent reperfusion therapies, 91% of patients (141/155) arrived by ambulance, 79.2% (122/155) had neurological improvement at discharge, and 60.6% (94/155) had an mRS 0-2 at 3 months. Less than 5% of patients had direct early access to the rehabilitation center. Conclusion: Our study demonstrated that the implementation of NSP with organized protocol-driven inpatient care led to significant advancement in acute stroke service performance. We believe that our report will serve as a model for achieving advanced and structured stroke care in a resource-limited context and contribute to the future development of the healthcare system in our country.